Effects of effective Microorganisms on soil pH and nut yield of coconut trees in the taniaga plantation located in Sandakan, Sabah, Malaysia - Clament Chin Fui Seung; Lum Mok Sam; Ricky Yakub Ganang; Bayre Suadik (Penerbit Universiti Malaysia Sabah, 2025)
Prolonged or overuse of chemical fertilizers can cause soil acidification in coconut plantations. This study investigated the effects of Effective Microorganisms (EM) on soil pH and nut yield of coconut trees in the Taniaga Plantation, Sandakan, Sabah, Malaysia. Conducted over 12 months (June 2023– May 2024), the experiment evaluated five treatments, including various EM application rates and dolomite, in a randomized design using Tagunan coconut varieties. Results showed that EM significantly increased soil pH from strongly acidic levels (3.82–4.08) to a more favorable range (up to 5.23), particularly in treatment T4 (8 kg EM). However, the highest nut yield was recorded in T3 (4 kg EM), indicating an optimal balance between microbial activity and nutrient availability. In contrast, dolomite treatment resulted in lower yields due to potential nutrient imbalances and suboptimal pH levels. The findings suggest that EM enhances soil health, buffers pH, and improves coconut yield, with 4 kg EM per tree identified as the most effective treatment. Continued EM application is recommended for sustainable coconut production and improved soil fertility.